2006
DOI: 10.1152/ajprenal.00195.2006
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of epithelial ion channels with the actin-based cytoskeleton

Abstract: The interaction of ion channels with the actin-based cytoskeleton in epithelial cells not only maintains the polarized expression of ion channels within specific membrane domains, it also functions in the intracellular trafficking and regulation of channel activity. Initial evidence supporting an interaction between epithelial ion channels and the actin-based cytoskeleton came from patch-clamp studies examining the effects of cytochalasins on channel activity. Cytochalasins were shown to either activate or ina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
70
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(73 citation statements)
references
References 130 publications
(179 reference statements)
3
70
0
Order By: Relevance
“…It has been reported that both depolymerization of the actin cytoskeleton with cytochalasin-D and stabilization of the actin network with phalloidin suppresses Ano1 currents (42). A number of ion channels have been shown to interact with the actin cytoskeleton (43). It is particularly interesting that another epithelial Cl − channel, CFTR, interacts with some of the same proteins that Ano1 interacts with, notably ezrin and NHERF1.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that both depolymerization of the actin cytoskeleton with cytochalasin-D and stabilization of the actin network with phalloidin suppresses Ano1 currents (42). A number of ion channels have been shown to interact with the actin cytoskeleton (43). It is particularly interesting that another epithelial Cl − channel, CFTR, interacts with some of the same proteins that Ano1 interacts with, notably ezrin and NHERF1.…”
Section: Discussionmentioning
confidence: 99%
“…Actin microfilaments are responsible for surface expression, functional activity and intracellular trafficking of numerous ion channels (for a review, see Mazzochi et al 2006). They may also be involved in the targeting and/or internalization of surface receptors, including HE6/ GPR64.…”
Section: Discussionmentioning
confidence: 99%
“…That nanoparticles can have a regulatory impact on ion channels was shown for SiO 2 nanoparticles on TRP4 channels in a neuronal cell line. 52 Ion channels are tightly connected to the cytoskeleton, especially to the actin fibers, 19 either through bindings between specialized proteins and the fibers 53 or through interaction between fibers and lipid rafts, in which the channels can be located. 20 These connections allow the channels to maintain their function in the fluidic environment of the membrane.…”
Section: Discussionmentioning
confidence: 99%